Anti-Tumor Potential of Gymnema sylvestre Saponin Rich Fraction on In Vitro Breast Cancer Cell Lines and In Vivo Tumor-Bearing Mouse Models - Abhinav Raj Ghosh; Abdulrhman Alsayari; Alaa Hamed Habib; Shadma Wahab; Abhishek P. R. Nadig; Misbahuddin M. Rafeeq; Najat Binothman; Majidah Aljadani; Ibtesam S. Al-Dhuayan; Nouf K. Alaqeel; Mohammad Khalid; Kamsagara Linganna Krishna (MDPI AG, 2023)
Gymnema sylvestre (GS) is a perennial woody vine native to tropical Asia, China, the Arabian Peninsula, Africa and Australia. GS has been used as a medicinal plant with potential anti-microbial, anti-inflammatory and anti-oxidant properties. This study was conceptualized to evaluate the cytotoxicity potential of Gymnema sylvestre saponin rich fraction (GSSRF) on breast cancer cell lines (MCF-7 and MDA-MB-468) by SRB assay. The anti-tumor activity of GSSRF was assessed in tumor-bearing Elrich ascites carcinoma (EAC) and Dalton's lymphoma ascites (DLA) mouse models. The anti-oxidant potential of GSSRF was assessed by DPPH radical scavenging assay. The acute toxicity of GSSRF was carried out according to OECD guideline 425. The yield of GSSRF was around 1.4% and the presence of saponin content in GSSRF was confirmed by qualitative and Fourier transform infrared spectroscopic (FTIR) analysis. The in vitro cytotoxic effects of GSSRF on breast cancer cell lines were promising and found to be dose-dependent. An acute toxicity study of GSSRF was found to be safe at 2000 mg/kg body weight. GSSRF treatment has shown a significant increase in the body weight and the life span of EAC-bearing mice in a dose-dependent manner when compared with the control group. In the solid tumor model, the doses of 100 and 200 mg/kg body weight per day have shown about 46.70% and 60.80% reduction in tumor weight and controlled the tumor weight until the 30th day when compared with the control group. The activity of GSSRF in both models was similar to the cisplatin, a standard anticancer agent used in the study. Together, these results open the door for detailed investigations of anti-tumor potentials of GSSRF in specific tumor models, mechanistic studies and clinical trials leading to promising novel therapeutics for cancer therapy.